APAKAH HARGA SAHAM DAPAT DI PENGARUHI OLEH INTELEKTUAL CAPITAL DAN OPINI AUDIT - Supriadi, Adi (Universitas Logistik dan Bisnis Internasional, 2024)
This research aims to determine and obtain empirical evidence of the influence of intellectual capital and audit opinion on share prices. This research uses quantitative research using descriptive methods. The population in this study includes Infrastructure, Utilities and Transportation listed on the Indonesia Stock Exchange, namely 79 companies. The sampling technique used was purposive sampling by obtaining 60 data. The analysis method used a multiple linear regression model which was processed and analyzed using the IBM Statistical Package for Social Sciences (SPSS) version 25 program. The results of the study showed that intellectual capital and audit opinion had no effect. on share prices either simultaneously or partially. This research is expected to provide benefits to future researchers as additional material for consideration, as a reference, as material for analysis and this research is expected to be useful for companies, from the input and results of this research it can provide information to certain parties in the company regarding intellectual capital and opinions regarding stock price. The limitation of the research is that this research only focuses on certain companies that match the research criteria so that the research results cannot be generalized to all infrastructure, utilities and transportation listed on the Indonesia Stock Exchange. Investors and potential investors who want to invest their shares in a company should first look at the financial condition and fundamentals of the company they will choose.